Bahasa Inggris: Bahasa Indonesia - M. Arifurrahman Hasyim; Mochammad Bagja Agung Nugraha Zainaldy (Bahasa dan Sastra Arab, Fakultas Adab dan Humaniora, UIN Sunan Gunung Djati, 2026)
This study examines how Yusuf al-Siba‘i’s Naib Izrail turns death into a narrative mechanism that destabilizes the legitimacy of office, honor, and public recognition. Previous studies have identified its religious messages, social criticism, representation of the Angel of Death, and authorial subjectivity, but have not explained how the novel withdraws symbolic recognition from dominant actors. Using Pierre Bourdieu’s concepts of doxa, symbolic capital, symbolic power, and legitimate language, the study applies qualitative close reading to narration, dialogue, characterization, and episodes involving Yusuf, Izrail, elites, and ordinary people. The findings show that worldly authority is constructed as a doxic order that misrecognizes status as moral worth; Izrail’s authorized speech reverses human hierarchies; death prevents elite capital from converting into immunity; and fantastic satire exposes manipulation, materialism, and governmental abuse. Death is therefore not symbolic power itself, but a counter-classificatory device that interrupts doxa and reveals human legitimacy as contingent within society.